Immunohistochemical Labelling for Cyclo-oxygenase-2: Does the Positive Control Guarantee Standardized Results?. Issue 2 (February 2016) - Belluco, S.; Carnier, P.; Castagnaro, M.; Chiers, K.; Millanta, F.; Peña, L.; Pires, I.; Queiroga, F.; Riffard, S.; Scase, T.; Polton, G.
Summary: Since the identification of cyclo-oxygenase-2 as a potentially important therapeutic target in veterinary oncology, numerous studies on its expression have been conducted. Unfortunately, results have been heterogeneous and conclusions are difficult to draw. We tested the ability of a defined positive control to guarantee reproducibility of results among different laboratories. Valid positive controls were defined by positivity of the renal macula densa without background labelling. Fifteen colorectal tumours and 15 oral squamous cell carcinomas were labelled immunohistochemically by six European laboratories. Slides were evaluated in blinded fashion for percentage of positive cells and labelling intensity by three pathologists, and results were analyzed statistically for reproducibility and inter-reader variability. Macula densa positivity was an insufficiently sensitive control to guarantee reproducible results for percentage of positive cells and labelling intensity. Inter-reader variability was proven statistically, making the case for image analysis or other automated quantitative evaluation techniques.